The Effect of Training and Work Discipline on the Performance of Criminal Research Unit Members at the Seribu Islands Police - Rama Sanny Kurniawan; Harries Madiistriyatno; Widya Nengsih (Dinasti International Journal of Digital Business Management, 2026)
Member performance is a key factor in supporting the effectiveness of law enforcement duties, especially in the Criminal Investigation Unit (Sat Reskrim) of the Thousand Islands Police, which has the characteristics of an archipelago with complex operational challenges. The high demands for professionalism and responsiveness of law enforcement officers require quality training and strong and consistent work discipline. This study aims to analyze the effect of training and work discipline on the performance of members of the Criminal Investigation Unit of the Thousand Islands Police, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 96 members of the Criminal Investigation Unit of the Thousand Islands Police as research respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that partially training has a positive and significant effect on member performance with a t-value of 6.162 and a significance level of 0.000. In addition, work discipline also has a positive and significant effect on member performance with a t-value of 5.193 and a significance level of 0.000. Simultaneously, training and work discipline have a significant effect on member performance, as indicated by the F-count value of 37.733 with a significance level of <0.001. The coefficient of determination (R Square) of 0.448 indicates that training and work discipline are able to explain 44.8% of the variation in member performance, while the rest is influenced by other factors outside the research model. This study confirms that continuous improvement in the quality of training and consistent enforcement of work discipline are strategic factors in improving the performance of members of the Thousand Islands Police Criminal Investigation Unit